Compliance of Appointment, Antidiabetic Treatment, and Diet in Type 2 Diabetes Mellitus Patients at Private Diabetes Clinic - Kiran Piparva; Anil Singh; Nirav Joshi (Dubai Diabetes and Endocrinology Journal)
Context: India is an epicenter of type 2 diabetes mellitus (T2DM) in the entire world. Compliance is essential for chronic diseases treatment and has a significant impact on health and health care costs. The current study was planned to assess compliance to the appointment, treatment, and diet in T2DM patients at a private diabetic clinic in Rajkot city. Aims: The aim was to assess compliance to physician’s appointment, antidiabetic treatment, and diet among T2DM patients attending private diabetic clinic at Rajkot city. Settings and Design: This was an interview-based, prospective study done at a private diabetes clinic. Methods and Material: T2DM patients (>18 years) of either gender who were on antidiabetic treatment (at least 3 months before enrollment) at a private outpatient diabetic clinic during 2019 were included after ethical approval and obtaining informed consent. Juvenile diabetes, gestational diabetes, and noncompliant T2DM patients were excluded. Statistical Analysis Used: The χ2 test was used for the statistical association of sociodemographic and disease variables with compliance using GraphPad version 7 (p value <0.05 was considered significant). Results: Of 370 enrolled patients, 21 patients were lost to follow-up (noncompliant). From 349 T2DM patients, the majority of patients were in the middle age-group (60%, 41–60 years), preobese and obese (69.99%), and with comorbidity (42.7%). Compliance to appointment, treatment, and diet was observed above 85% in this study. Old age (>60 years) was significantly associated with poor appointment compliance, and comorbidity is significantly associated with the poor appointment, treatment, and diet compliance. An increasing number of comorbidities were significantly associated with poor appointment compliance. Conclusions: A higher compliance to appointment, treatment, and diet was achieved.